Acetylation of vitamin E by Candida antarctica lipase B immobilized on different carriers - Torres, Pamela; Reyes-Duarte, Dolores; López-Cortés, Nieves; Ferrer, Manuel; Ballesteros Olmo, Antonio; Plou Gasca, Francisco José (Process Biochemistry, 2009)
We describe for the first time the enzymatic acylation of the phenolic group of tocopherols (vitamin E) by transesterification with vinyl acetate in 2-methyl-2-butanol (2M2B). Out of 15 hydrolases screened, only the lipase B from Candida antarctica (Novozym 435) catalyzed the acylation. The acetylation of -tocopherol was faster than that of -tocopherol, probably due to its lower methylation degree. A series of experiments using (R)-Trolox and p-cresol as competitive acceptors of tocopherols showed that reaction rate notably diminished when increasing acceptor size. To maximize the potential of this reaction, three immobilization carriers for C. antarctica lipase B were studied: the ion-exchange resin Lewatit (the support in Novozym 435), a biodegradable polymer (Purasorb) and polypropylene (Accurel EP100). The acetylation of -tocopherol was faster with the enzyme immobilized in polypropylene, which was correlated with its higher porosity. A mixture hexane/2M2B 90:10 (v/v) was found to be the optimum medium composition, as it represents a compromise between substrates solubility and biocatalyst efficiency. The acylation process was no enantioselective, probably due to the fact that the chiral centers are separated from the phenolic group by a minimum of six bonds. We are grateful to Morten Christensen and Lotte Andersen (Novozymes A/S) for technical help. We thank Ana V. Ugidos and Soledad Peña (Biotecnologías Aplicadas, BTSA, Spain) for technical information and suggestions. We are grateful to Dr. Karl Hult (Royal Institute of Technology, Sweden) for practical suggestions. We thank Ramiro Martínez (Novozymes A/S Spain) for technical help. We thank Dr. M. L. Rojas-Cervantes (UNED, Spain) and Dr. M. Yates (ICP, CSIC, Spain) for porosity measurements. This research was supported by the Spanish CSIC (Project 200680F0132) and MEC (Project BIO2002-00337). Peer reviewed